Pediatric to adult rheumatology transition: Success rates, influencing factors, and evolving diagnoses and treatments - Tuba Demirci Yıldırım; Rana İşgüder and Ezgi Karaçura and Yeşim Erez and Balahan Makay and Fatoş Önen and Şevket Erbil Ünsal and İsmail Sarı (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the rate of successful transitions, identify factors associated with early versus late transitions, and diagnosis and treatment changes after transition into adult rheumatology. Patients and methods: In this retrospective study, patients with childhood-onset rheumatic diseases who transitioned from pediatric to adult rheumatology care between January 2013 and January 2023 were screened for a successful transition. Successful transitions were defined as maintaining annual visits to the adult rheumatology clinic after transition. Early transition was defined as less than three months between the last pediatric and first adult rheumatology visits. Results: Out of 2,552 referred patients, 210 (8.2%) patients (117 females, 93 males; mean age: 25.2±5.6 years; range, 18 to 44 years) transitioned successfully. Juvenile idiopathic arthritis and familial Mediterranean fever were the most prevalent rheumatic diseases. The median transition time was four months (interquartile range, 1 to 13 months) in patients with successful transition, and the early transition rate was 46.7%. Receiving biologic disease-modifying antirheumatic drugs was found to be associated with early transition (28.6% vs. 17.0%, p=0.040), and higher education levels and familial Mediterranean fever diagnosis were found to be associated with late transition. The treatment was changed for about half of the patients after transition to adult rheumatology. Patients with juvenile idiopathic arthritis were reclassified in 25 (31.6%) patients as rheumatoid arthritis, in 22 (27.8%) patients as ankylosing spondylitis, in 20 (25.3%) patients as nonradiographic axial spondyloarthritis, and in eight (10.1%) patients as psoriatic arthritis. Conclusion: A successful transition to adult rheumatology is essential for adolescents and young adults with childhood-onset rheumatic diseases. The successful transition rate in this study was relatively low, highlighting the need for standardized transition programs.